2014
DOI: 10.1007/s13277-014-2519-3
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A inhibits the migration and invasion of human lung cancer cells via inactivation of the Akt signaling pathway with downregulation of MMP-1/-3 expression

Abstract: Licochalcone A (LicA), a major phenolic constituent of Glycyrrhiza inflata, has been reported to exhibit anti-tumor, anti-inflammatory, and anti-metastatic properties in various cancer cells and animal models. The aim of this study was to determine the anti-tumor effects of LicA on lung cancer cells. The results indicated that LicA exhibited effective inhibition of cell migration and invasion of A549 and H460 cells under non-cytotoxic concentrations. Furthermore, LicA was also found to significantly inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Extracts from Ecklonia cava that were enriched in polyphenol suppress the migration of lung A549 cells via the downregulation of AKT and MMP-2 activities (25). In addition, licochalcone A attenuated the migration of lung A549 cells by the downregulation of the AKT activity and suppression of the MMP-1 and -3 expression (24). In the present study, treatment with naringenin reduced the phosphorylation of AKT in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Extracts from Ecklonia cava that were enriched in polyphenol suppress the migration of lung A549 cells via the downregulation of AKT and MMP-2 activities (25). In addition, licochalcone A attenuated the migration of lung A549 cells by the downregulation of the AKT activity and suppression of the MMP-1 and -3 expression (24). In the present study, treatment with naringenin reduced the phosphorylation of AKT in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…However, it blocked the activities of AKT by wortmannin and also suppressed MMP-2 expression (23). Previous reports have demonstrated that polyphenol isolated from vegetables and fruits inhibited lung cancer migration through the reduction of the AKT activity (24,25). Extracts from Ecklonia cava that were enriched in polyphenol suppress the migration of lung A549 cells via the downregulation of AKT and MMP-2 activities (25).…”
Section: Discussionmentioning
confidence: 98%
“…The data from the present study demonstrated that Licochalcone A decreases cell viability, induces apoptosis and increases the caspase-3 activity in MCF-7 cells. Previous studies have demonstrated that Licochalcone A suppresses growth of human esophageal carcinoma (14), human lung cancer (15) and human oral cancer cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LicA suppressed the expression of NF-κB and its binding to the uPA promoter [109]. Others reported that LicA effectively inhibited migration and invasion of A549 and H460 lung cancer cells [110]. The compound also significantly inhibited the protein and gene expression of MMP-1 and MMP-3 in A549 cells.…”
Section: Antioxidant Effectsmentioning
confidence: 93%
“…The compound also significantly inhibited the protein and gene expression of MMP-1 and MMP-3 in A549 cells. Treatment of A549 cells with LicA suppressed phosphorylation of Akt, an effect, along with inhibition of migration and invasion, that was reversed by treatment with LY294002 (PI3-K inhibitor) or transfection with constitutive active-Akt i [110].…”
Section: Antioxidant Effectsmentioning
confidence: 99%